Heidegger and the problem of the nothingness. His criticism of Nietzsche’s position - Ávila Crespo, Remedios (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The following paper takes as its theme the philosophical problem of nothingness in the thought of Heidegger. The paper has two purposes: On one hand, to clarify the position that metaphysics has in Heidegger; and, on the other, to show the relationship he establishes between metaphysics and nihilism.
Keywords: metaphysics; nihilism; Heidegger